Abjection, identity and the enigmatic message: embodied meanings and social constructions. (1st July 2019) - Charles, Marilyn
Abstract : Identity is built upon the early interactions with caretakers through whom we internalize a felt-sense of what it means to be ourselves, including values and judgments that have been passed along the generations. Psychoanalytic theory and the attachment literature help us to understand some of the more subversive elements of that transmission process, ways in which unprocessed trauma and unresolved mourning provides a vehicle for passing along positive and negative aspects of personal, familial and cultural aspects of identity across the generations. Because that transmission process directly impacts ways in which oppression and marginalization skew meanings for future generations, it is important that we consciously recognize and work with the projective processes as they play out in our children and in ourselves. In this paper, I discuss ways in which projection and unprocessed shame can inhibit the type of active reflection required for ethical behavior and democratic process.